A The Roman Emptio-Venditio as a Modern Expression of The Electronic Contracting - Chavdar, Kimo; Stojanovski, Dushko; Pavlova, Natasha (International Scientific Journal Vision, 2017)
This paper analyzes the sales agreement or ,emptio venditio” in Roman law, but from the aspect of the new modern age, the age of the Internet and the accessibility of the internet in every home. In that sense, the Electronic Contract is defined as an agreement presented and consummated entirely in an on-line environment; most often on the Internet. In order to form a contract several conditions must be met. In this paper as a part of the Electronic Contract the terms Electronic signing of the agreement and e-commerce are also analyzed together with the way these requirements are carried out in order to form a contract. The uniqueness of forming an electronic contract results in specific measures for the protection of intellectual property rights. A brief overview of the legislation in the Republic of Macedonia regarding the forming of agreements in electronic form is given at the end of the paper.